A Study on the Surface Hardness Obtained by Nitriding with a Plasma Focus Machine - Teh, Thiam Oun; Arwinder, Singh*; Jalil, Ali; Ng, Chee An; Ng, Xue Yinn; Wong, Jun Wen; Saw, Sor Heoh; Lee, Sing (2019)
A dense plasma focus (DPF) machine, being a source of a powerful ion beam, can be useful in the modification of the surface properties of materials. Experimental investigations were carried out with a 3.3 kJ Mather-type DPF operating in nitrogen at a low chamber pressure with low carbon steel as the target material. It was found that the DPF ion beam implanted nitrogen onto the steel surface thereby causing a marked increase in surface hardness. The variation of pressure and target distances appear to affect the outcome of this nitriding technique with optimum hardness reached at the pressure setting of 1 Torr and at a target distance of 40 mm from the anode.